Cefovecin pharmacokinetics after single‐dose intramuscular administration in cheetahs (Acinonyx jubatus). Issue 5 (28th March 2021) - Yu, Jennifer H.; Papich, Mark G.; Garcés Torres, Rodrigo; Emerson, Jessica; Kinney, Matthew E.; Helmick, Kelly; Crosier, Adrienne; Sanchez, Carlos R.; Murray, Suzan
Abstract: Cefovecin is a third‐generation cephalosporin with potential value for use in exotic felids due to its long duration of action. A sparse sampling protocol was implemented with 18 zoo‐housed cheetahs ( Acinonyx jubatus ) to evaluate the pharmacokinetics of cefovecin (Convenia ® ) after a single 8 mg/kg intramuscular injection. Blood was collected serially for 15 days following administration, and plasma cefovecin concentrations were determined using high‐pressure liquid chromatography with ultraviolet detection. Pharmacokinetic parameters were estimated using population pharmacokinetic methods and non‐linear mixed effects modeling (NLME). Cefovecin was well tolerated by all cats, with no adverse effects observed. Peak plasma cefovecin concentration was 84.75 µg/ml, with a mean residence time of 207.9 h and an elimination half‐life of 144.1 h (6.00 days). Plasma concentrations of cefovecin were maintained >7 µg/ml in all individuals for the entire study duration (15 days). These concentrations are lower, and the half‐life slightly shorter, than the values reported for domestic cats. Cefovecin was highly protein‐bound (approximately 99.9%) in cheetah plasma, which is nearly identical to domestic cats. These results indicate that cefovecin is potentially useful as a long‐acting antibiotic in cheetahs.